Emotional Involvement in EFL Speaking Tasks: Implementing Project-Based Learning in an Indonesian Higher Education Context - Nur Aeni Kasim; Antonius Ali Wutun; Nurfitriyah Halim; Adriani Jihad; Rita Roswita Duyo; Sinta Dewi Anggung (Universitas Sulawesi Barat, 2026)
Improving students’ ability to speak English confidently and fluently remains a challenge in many higher education institutions, including STKIP YPUP Makassar. Although speaking is a core skill in English education programs, many learners still struggle to express themselves effectively. To address this, Project-Based Learning (PBL) has emerged as a promising method, offering students the chance to actively use language through meaningful and collaborative tasks. This study aims to examine the students’ emotional involvement in learning speaking through Project-Based Learning approach at the students of STKIP YPUP in 2024/2025 academic year. The research method used is descriptive qualitative, with data collection techniques including observation, interviews, documentation, and project outputs produced by the students. This study investigates how PBL influences students' emotional engagement and speaking development in an ESL context. Using a descriptive qualitative approach, the research gathered data through classroom observations, interviews with students, analysis of learning documents, and assessments of various student-led projects such as group presentations, performances, and interviews conducted in English. The results show that integrating PBL into speaking classes not only boosted students’ participation and motivation but also helped them become more confident and expressive in using the language. In addition, students reported feeling more connected to the learning process, and they developed skills such as teamwork, accountability, and critical thinking. Overall, the findings suggest that PBL can be an effective and engaging alternative for improving speaking instruction in higher education ESL settings.